Navigating the Tensions Between Sharia and Human Rights in Regional Legislation - Fadhil, Moh.; Herman, Herman; Wagner, Ivan; Simbolon, Subandri; Harefa, Safaruddin (De Jure: Jurnal Hukum dan Syari'ah, 2024)
The legacy of past conflicts has prompted the emergence of a civil society movement with the objective of transforming Pontianak City into a Human Rights City. This movement is pursuing this goal through the drafting of a Regional Regulation on Tolerance. Nevertheless, the legislative and political process within the Regional Houses of Representatives has given rise to paradigmatic debates concerning the concept of human rights. This article aims to elucidate the paradigmatic conflict between state actors and civil society during the drafting of the Regional Regulation on Tolerance in Pontianak City. The field study presented in this article is based on active participation in public hearings and dialogues between the Regional Houses of Representatives and civil society. The study employs a socio-legal approach, which reveals a contention between two distinct paradigms: the positivist paradigm (naive realism), as represented by state actors, and the critical paradigm (historical realism), as advocated by civil society. The Regional Houses of Representatives, as state actors, oppose the institutionalization of tolerance on the grounds that the Eurocentric concept of human rights may conflict with Sharia and local culture. In contrast, civil society views tolerance as a tool for addressing structural inequalities inherited from past conflicts. The inability of the two parties to reach a consensus led to the failure to ratify the Regional Regulation on Tolerance, which prioritizes human rights. This outcome underscores that human rights have not been a primary consideration in the formulation of local regulations on tolerance. This attitude contrasts with international and national human rights law, which has the effect of neglecting the aspiration to become a human rights city. This research contributes to changes in the strategy of the civil society movement in advocating for human rights law in regional policy.